2011
DOI: 10.1063/1.3660270
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of silicon optical fibers

Abstract: Influence of rapid thermal annealing on a 30 stack InAs/GaAs quantum dot infrared photodetector J. Appl. Phys. 94, 5283 (2003); 10.1063/1.1609634 Initial growth step and annealing effect of Ta 2 O 5 formed by anodization of Ta foil in an ammonium tartrate electrolyte J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…It is not the intent of this work to assert that core geometry is the singular solution to enhanced crystallinity and, therefore, reduce the loss in these crystalline core optical fibers. Recent work [24] has shown that annealing of silicon fibers also can greatly enhance single crystallinity. Accordingly, the continued optimization of these fibers will almost certainly rely on multiple factors that include, but are likely not limited to the influences of core geometry, annealing, and controlled doping.…”
Section: Resultsmentioning
confidence: 99%
“…It is not the intent of this work to assert that core geometry is the singular solution to enhanced crystallinity and, therefore, reduce the loss in these crystalline core optical fibers. Recent work [24] has shown that annealing of silicon fibers also can greatly enhance single crystallinity. Accordingly, the continued optimization of these fibers will almost certainly rely on multiple factors that include, but are likely not limited to the influences of core geometry, annealing, and controlled doping.…”
Section: Resultsmentioning
confidence: 99%
“…However, the loss values for the p-Si fibres fabricated by the MCD method are not too far behind, most likely due to the large crystal grains that are produced via the drawing method [14,21,32]. Further improvements to the p-Si core materials can be made post-process using thermal [41,42] or laser-induced annealing treatments [43] and in fact, the lowest losses reported for the MCD fibres were obtained after processing with a CO 2 laser [44]. Figure 7(b) presents the lowest loss values that have been reported for germanium core fibres.…”
Section: Transmission Lossesmentioning
confidence: 99%
“…[ 128 ] Extensive work has also been performed to elucidate and control nucleation and grain growth, in order to extend the length of single crystal domains along the fi ber axis. [129][130][131] Note also that Se and Te cores have recently been co-drawn inside phosphate glasses, which paves the way towards integrating semiconducting materials at a novel temperature range. [ 44,132 ] To realize optoelectronic fi bers with these materials, however, the diffi culty remains of fi nding compatible materials to act as electrodes that do not mix or react with the molten semiconductor during drawing.…”
Section: Crystalline Semiconductor-based Optoelectronic Fibersmentioning
confidence: 99%